Determination of dioxin-like polychlorinated biphenyls in soil and moss from Fildes Peninsula, Antarctica - Wang Qiang; Shi YeHong; Hu JianXin; Yao ZiWei; Fang XueKun; Dong YiAn (Chinese Science Bulletin, 2012)
Dioxin-like polychlorinated biphenyls (PCBs) are a class of toxic and persistent chemicals that are often found in the environment. The determination of dioxin-like PCBs in Fildes Peninsula, Antarctica, is reported in this paper. Dioxin-like PCBs were widely distributed in Antarctic soil and moss with concentration of 2.23-27.2 pg/g in soil and 10.4-812 pg/g in moss. The highest concentrations were found in the Ardley Island area and the lowest concentrations on the west coast. The contribution of PCB-118 to the I (12)PCBs pound ranged from 36.0% to 69.6% in soil, and 17.2% to 43.4% in moss. The congener specific patterns in soil and moss were similar. Long-range atmospheric transport is thought to be the main source of PCBs detected on King George Island. The I (12)PCBs pound toxic equivalent (TEQ) in soil was 0.400x10(-3) to 516x10(-3) pg (TEQ)/g with a mean value of 147x10(-3) pg (TEQ)/g. PCB-126 had the largest contribution (81.1%) to the I (12)PCBs pound TEQ in soil. The I (12)PCBs pound TEQ in moss ranged from 2.90x10(-3) to 1.19 pg/g with a mean value of 0.482 pg/g. PCB-126 was also the largest contributor (91.4%) to the I (12)PCBs pound TEQ in moss. The mean TEQ in moss was about 40 times that in soil. Multidisciplinary Sciences SCI(E) 0 ARTICLE 9 992-996 57